New distributional data on Haemogregarina stepanowi (Apicomplexa) and Placobdella costata (Hirudinea) parasitising the Sicilian pond turtle Emys trinacris (Testudines) - Rita Scardino (PAGEPress Publications, 2021)
The host-parasite system “Emys trinacris – Placobdella costata – Haemogregarina stepanowi” is known for Sicily, but scarce information is available to date about the distribution of the two parasites on the island. Therefore, an extensive sampling effort through visual census and collection and analysis of blood smears of the endemic Sicilian pond turtle E. trinacris was carried out in 46 water bodies scattered throughout mainland Sicily. Our findings revealed that the distribution of both parasites is limited to the Nebrodi area, where the infection of H. stepanowi has shown a high incidence on the local turtle populations. Our data suggest no correlation between the current distribution of the two parasite species and environmental features. The current distribution of H. stepanowi and P. costata seems not to be relictual, but rather the outcome of a recent colonisation process. Considering the possible negative impact of both H. stepanowi and P. costata on their turtle host, their long-term effect on E. trinacris should be investigated.